2021
DOI: 10.36740/wlek202103230
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hygienic Assessment of Working Conditions and Occupational Risk in the Application of Pesticides (On the Example of Fungicide Amistar Extra 280, Sc) Using Different Types of Sprayers

Abstract: The aim: Was a comparative hygienic assessment of working conditions and occupational risk in the application of fungicide Amistar Extra 280, SC using slotted and injector sprayers. Materials and methods: Sprayers Super Poly 110-04 (variant №1) and Guardian Air GA110-04 (variant № 2), and certified equipment were used. The occupational risk was assessed in accordance with the methodological recommendations proposed by the L.I. Medvedia Scientific Center for Preventive Toxicology, Food and Chemical Safety speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Today, epidemiological and experimental data on the impact of pesticides on the health and morbidity of workers and the population are accumulating, not only as factors that have a pronounced effect, but also as low-intensity factors. The reason for this is the progressive saturation of their production and non-production environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Today, epidemiological and experimental data on the impact of pesticides on the health and morbidity of workers and the population are accumulating, not only as factors that have a pronounced effect, but also as low-intensity factors. The reason for this is the progressive saturation of their production and non-production environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A simple understanding of the distance from, the duration of the application, and the protections in place for the applicator could make the position of UASS operator exposure a relatively simple academic exercise. In terms of task differences, Borysenko, Antonenko et al (2021) showed that exposure potential was higher for the UASS refueler compared to the pilot. This difference was due to longer exposure times for refuelers, with an exposure time of 42-45 min versus 28-30 min for the pilot.…”
Section: Operator Exposurementioning
confidence: 99%
“…Традиційний авіаційний метод внесення пестицидних препаратів зазвичай передбачає використання спеціально обладнаних літаків, гелікоптерів, мотодельтапланів, які можуть швидко й ефективно покривати великі площі посівів. Однак даний спосіб внесення може становити низку ризиків як для навколишнього середовища, так і для здоров'я людей [2,3,4].…”
Section: Analysis Of the Dynamics Of The Assortment Of Pesticides Per...unclassified